Influenza virus vaccine expressing fusion and attachment protein epitopes of respiratory syncytial virus induces protective antibodies in BALB/c mice - Bian, Chengrong; Liu, Shuzhen; Liu, Na; Zhang, Guangzhou; Xing, Li; Song, Yingwei; Duan, Yueqiang; Gu, Hongjing; Zhou, Ya; Zhang, Peirui; Li, Zhiwei; Zhang, Keming; et al. (Antiviral research, 2014)
•A recombinant influenza virus rFlu/RSV/F+G containing RSV F and G protein epitopes was generated.•rFlu/RSV/F+G showed specific antibody response against influenza virus and RSV in mice.•rFlu/RSV/F+G might elicit Th1-type cellular immune response against RSV.•rFlu/RSV/F+G could induce immune protective effect against influenza virus and RSV. Respiratory syncytial virus (RSV) is an important viral pathogen that causes life-threatening respiratory infections in both infants and the elderly; no vaccines are at present available. In this report, we examined the use of influenza virus as a vehicle for production of an experimental RSV vaccine. We used reverse genetics to generate a recombinant influenza A virus with epitopes from the RSV fusion (F) and attachment (G) proteins (rFlu/RSV/F+G) in the influenza virus nonstructural (NS1) protein gene. Expression of RSV F+G epitope proteins was confirmed by Western blotting, and no changes in viral morphology were evident following examination by electron microscopy. BALB/c mice immunized intranasally with rFlu/RSV/F+G showed viral-specific antibody responses against both influenza and RSV. Total IgG, IgG1, IgG2a and IgA were measured in mice immunized with rFlu/RSV/F+G, revealing robust cellular and mucosal immune responses. Furthermore, we found that rFlu/RSV/F+G conferred protection against subsequent influenza and RSV challenges, showing significant decreases in viral replication and obvious attenuation of histopathological changes associated with viral infections. These findings suggest that rFlu/RSV/F+G is a promising vaccine candidate, which should be further assessed using cotton rat and primate models.